2015
DOI: 10.1016/j.jct.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of solid phases containing rare earth oxides

Abstract: This paper is dedicated to the memory of Lester R. Morss (1940-2014), a wonderful colleague and friend who contributed extensively to the thermodynamics, chemistry, and physics of lanthanides and actinides and to service to the Department of Energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 142 publications
1
56
0
2
Order By: Relevance
“…For a detailed overview of the available calorimetric data for REEbearing solids, readers are referred to the recent review of Navrotsky et al (2015). Among the studies reported, most are devoted to synthetic phases important for industrial applications but of little relevance to hydrothermal processes.…”
Section: Thermochemistry and Solubility Of Hydrothermally Formed Ree-mentioning
confidence: 99%
“…For a detailed overview of the available calorimetric data for REEbearing solids, readers are referred to the recent review of Navrotsky et al (2015). Among the studies reported, most are devoted to synthetic phases important for industrial applications but of little relevance to hydrothermal processes.…”
Section: Thermochemistry and Solubility Of Hydrothermally Formed Ree-mentioning
confidence: 99%
“…This dataset comprises mineral data from Holland and Powell [55] and aqueous species from SUPCRT92 [36,57,63,64], with the recently updated internally consistent dataset of Miron et al [58] using the GEMSFITS code package [65]. Experimental data for REE chloride aqueous species were implemented using data from the study of Migdisov et al [35], the HCl dissociation constants of Tagirov et al [59], and the properties of REE(OH) 3 (s) compiled in the study of Navrotsky et al [56]. Data for aqueous REE carbonate and bicarbonate species were included using the theoretical predictions of Haas et al [36], which are currently the only available high temperature thermodynamic data for these species.…”
Section: Thermodynamic Dataset and Activity Modelsmentioning
confidence: 99%
“…Lastly, thermodynamic data for Lu(OH) 3 (s) are not available, as it was omitted in the Navrotsky et al [56] study. Cerium-, Dy-, Er-, and Tm(OH) 3 (s) thermodynamic data from the aforementioned study were derived from thermochemical data reported in Diakonov et al (1998) [76].…”
Section: Uncertainties and Assumptions Of The Modelmentioning
confidence: 99%
“…However, the main concern that arises with the use of REOs as a part of biomedical applications is their relatively unknown effects on the physiological system and research needs to be carried out if these oxides are too toxic for use as biomaterials [20]. Sm 2 O 3 is one such REO having density 8.347 g/cc with high hardness Vickers (438 HV), high melting temperature (2335 • C), elastic modulus (183 GPa), Gibbs free energy (−1734.9 KJ·Mol −1 ) [21,22]. Sm 2 O 3 is an important rare earth oxide and its current scope lies in the field of solar cells, semiconductor gas, biochemical sensors, laser and photonic devices, precision guided weapons, and is also an active catalyst for CO hydrogenation [23].…”
mentioning
confidence: 99%